Fieldwork Protocols for Anthropological Research in Mexico: Permissions and Dissemination. Issue 2 (2nd December 2020) - Rees, Martha W.
Abstract: The context of Mexican anthropology affects their institutional and ethical research protocols, and in turn, this context affects how foreign researchers should comply with these, in addition to the codes of their home professional associations and funders. This article examines research permissions and dissemination of results and products, in terms of Mexican protocols and the American Anthropological Association's Code of Ethics, using examples from U.S. and Mexican field research. The objective is to promote greater collaboration, mutual respect, and dissemination, while recognizing the obstacles that different conceptual, professional, and funding frameworks present.